Virtual Veneration: A Critical Inquiry into the Sacralization and Valorization of Digital Heritage in the Metaverse - Ifah Shandy; Kevin Setiawan; Khalil Jibran; Caelin Damayanti (Enigma in Cultural, 2025)
The emergence of the metaverse presents a paradigm shift for how cultural heritage is experienced and valued. While technical digitization is well-studied, the socio-cultural processes by which digital objects acquire profound, quasi-sacred meaning remain critically underexplored. This study undertakes a critical inquiry into "virtual veneration," examining the mechanisms through which digital artifacts are sacralized and valorized within metaverse environments. A sequential explanatory mixed-methods design was employed. Phase one involved a qualitative thematic analysis of three leading metaverse platforms (Decentraland, The Sandbox, VRChat) to identify key features of value creation. Phase two was a large-scale quantitative analysis of behavioral data from a diverse cohort of 10,000 users within the Virtual Artifact Interaction Model (VAIM), a controlled experimental environment. Acknowledging the philosophical limits of measuring "sacredness," we developed a composite "Index of High-Value Collective Attention" (HVCA) based on metrics of dwell time, interaction frequency, and social signal amplification to operationalize the behavioral markers of veneration. The qualitative analysis revealed three core themes: "The Architecture of Awe," "Ritualized Communitas," and "The Aura of Scarcity." The quantitative analysis demonstrated that "Community Narrative" was the most powerful predictor of an artifact's HVCA score (), far exceeding the impact of authenticity or scarcity. A significant synergistic effect was found between environmental conditions of "Exclusive Access" and "Ritualistic Interaction" (), confirming that architectural framing and social protocols work in concert. Social proof directed 65.4% of user attention, indicating that valorization is a socially contingent and path-dependent process. In conclusion, the sacralization of digital heritage is a complex socio-technical process contingent on platform design, community ritual, and perceived authenticity. However, this study concludes that these mechanisms, particularly when mediated by speculative economies, create a "networked aura" that functions as a political inversion of Walter Benjamin's original concept, re-ritualizing art for markets. The findings suggest the emergence of a "hyper-sacred"—emotionally potent but ontologically unmoored—posing profound ethical and philosophical questions for the future of cultural value.